Prof. dr hab. Jerzy Szydłowski - Gediga, Bogusław (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
29 cm
Keywords: Szydłowski, Jerzy (1931-1997; archaeologist); Polish archaeologists; personal biographies; history of Polish archaeology

Beiträge zur frühneolithischen Trichterbecherkultur im westlichen Ostseegebiet, red. Jürgen Hoika, Jutta Meurers-Balke, Neumünster 1994 : [recenzja] - Wierzbicki, Jacek (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
29 cm
Keywords: Neolithic -- Baltic Sea region; Neolithic cultures; Funnel Beaker culture; chronology of Funnel Beaker culture

Uzupełniające uwagi dotyczące wczesnośredniowiecznych gęśli z Opola - Malinowski, Tadeusz (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
ill. ; 29 cm
Keywords: early Middle Ages -- Poland; early medieval musical instruments; early medieval string instruments; gusle; Opole (Poland)

Animal bones as a source of Calcium for Mesolitic man - Lasota-Moskalewska, Alicja; Kobryń, Henryk; Sulgostowska, Zofia; Siemaszko, Jerzy; Brzozowski, Jerzy (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
Animal bone remains in most Mesolithic sites on the terrain of Poland are very often highly fragmented and burned. It seems that after having been burned they were ground or pulverised. Such state of bones suggests that Mesolithic man produced bone powder, which might have been consumed in order to supplement calcium level in diet. Calcium contents in water and nutritive products achievable in Mesolithic period was too low to cover the demand of the organism for this element. In medicine and veterinary there are also examples for use of untypical sources of calcium. From a general evaluation of a state of Mesolithic bone remains and probable calcium deficiency in diet we hypothesise that for Mesolithic man animal bones were a supplementary source of calcium
ill. ; 29 cm
Keywords: Mesolithic; diet; calcium; bone fragmentation

Mirkowice - another settlement of the Hamburgian culture at the Polish Plain - Chłodnicki, Marek; Kabaciński, Jacek (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
Paper discuss a new-discovered Hamburgian site located in the northern part of the Polish Lowland. A detailed technological and typological analysis of flint materials as well as stratigraphic and palaoenvironmental context of the settlement are presented. Exceptional geomorphological and stratigraphic position of the site - location at a dune in the close vicinity of the glacial trough, filled with biogenic sediments of the Bølling times - creates a unique possibility of a relatively complete reconstruction of the Early Late Glacial environment during the times of human occupation and a real chance of recovering artefacts made wood, bone and antler. Location of the Mirkowice site far north of the maximal extent of the last glacier is another argument in the discussion on spatial distribution of the Hamburgian settlement and generally supports a thesis of fast expansion of the Hamburgian to the north
ill. ; 29 cm
Keywords: Early Late Glacial; archaeological finds; palaeoenvironmental reconstruction; palaeoecology

Spis treści = Contents (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
29 cm
Keywords: archeologia Polski -- journal

Keltische Glasfunde im polnischen Gebiet - Karwowski, Maciej (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
Small glass objects, such as bracelets, rings, beads, pendants and fragments of vessels, are commonly found in the La Tène culture sites in the whole range of its occurrence. Some of the artefacts display no diagnostic features and in many areas they are defined in a wide chronological range. Distinctive Celtic forms are only the bracelets, ring-beads and possibly some of the so-called “mask-beads”. Glass bracelets recently became particularly significant as their precise chronology was arrived at. So far the unanswered question remains whether the Celts were able to produce glass themselves or whether they made ornaments from the imported semi-products. In Poland, Celtic glass artefacts constitute one of the most numerous non-ceramical categories of the finds connected with the La Tène culture. They make up the only such extensive group of objects wholly imported from the South during the middle and late La Tène periods. They are known to came from both the areas connected with local Celticsettlement as well as from the sites occupied by indigenous cultures (mainly Przeworsk and Oksywie cultures). In many cases, glass bracelets are the only objects which can be dated
ill. ; 29 cm
Keywords: glass; La Tène period; Poland; Celts (people); Celtic glass; glass finds; Celtic glass objects

Unikatowy dzban brązowy z Kowalewka, woj. poznańskie - Skorupka, Tomasz (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
ill. ; 29 cm
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; Roman period bronze jugs; Kowalewko (Poland)

Rola kontaktów ze Skandynawią w dziejach gospodarczych Słowian nadbałtyckich - Łosiński, Władysław (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
The author attempts to evaluate the significance of trade in the history of contacts between Scandinavians and Western Slavs. Their beginning may be dated back to the Vendel period but only at the end of that period and at the beginning of the Viking period did the contacts become more intensive. The trade comprised both luxury goods and bulk products and it centred in the manufacturing - trading open settlements. On the Slavic coast the newcomers from Scandinavia occupied the prominent position among the inhabitants of the settlements. The role of the Slavic element became more prominent in the late 9th cent. with thedevelopment of early towns, which became the centres of economic and social - political life of tribal communities. Further intensification of trade occurred in the late 10th cent., when the early-Piast monarchy entered the sphere of influence of the Baltic economic zone
29 cm
Keywords: Baltic Slavs and Scandinavians -- role of trade; Slavs; Scandinavian peoples; Slavic Lands and Scandinavia -- contacts; Slavic-Scandinavian relations; Slavic economy; early medieval trade

Struktura krewniacza i powiązania populacyjne ludności z Dziekanowic, stanowisko 2. Próba rekonstrukcji na podstawie materiału z cmentarzyska - Rysiewska, Teresa; Wrzesiński, Jacek (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
The present work attempts to reconstruct the kin structure and place of origin of the population using the cemetery in Dziekanowice, site 2. While the latter issue was not resolved due to very limited anthropometric data available, significant were the regularities in qualitative-quantitative and spatial distribution of such features as sex and age of individuals, geographical orientation of the graves, their deviation from the E-W axis and their equipment. The regularities indicate the family character of the cemetery, where the female graves of the wives of the family members were oriented differently than those of their husbands (heads towards west, similarly as the graves of the men from outside the local community). That supports the earlier hypothesis, frequently verified (cf. literature), that different orientation of graves in the early-Medieval cemeteries in Poland is a highly probable indicator of different family origins in the kin groups of patrilineal succession of kinship and of patrilocal marriage site
ill. ; 29 cm
Keywords: Dziekanowice 2; cemetery; kin structure; early medieval cemeteries; kinship and funeral customs and rites; social structures and funeral customs and rites